2016
DOI: 10.5603/cj.a2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of mortality and digoxin use in atrial fibrillation

Abstract: Background: There is growing controversy regarding the association between digoxin and mortality in atrial fibrillation (AF). (pooled HR 1.47;) than AF patients with heart failure (pooled HR 1.21; interaction p = 0.06). Conclusions: Digoxin use in AF is associated with increased risk of all-cause and cardiovascular mortalities. The effect size was larger for AF patients without heart failure than AF patients with heart failure. The study suggests further directed analyses to study the effect that is suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
2
28
1
2
Order By: Relevance
“…Since CTS antagonists such as pNaKitde 41 and rostafuroxin 42 have been developed, it will be interesting to test whether they are effective against atherosclerosis in vivo and therefore provide a novel therapeutic strategy. Finally, our findings may also provide a mechanistic basis for recent clinical reports of increased mortality rates in patients taking digoxin in the setting of chronic heart diseases 4345 .…”
Section: Discussionsupporting
confidence: 57%
“…Since CTS antagonists such as pNaKitde 41 and rostafuroxin 42 have been developed, it will be interesting to test whether they are effective against atherosclerosis in vivo and therefore provide a novel therapeutic strategy. Finally, our findings may also provide a mechanistic basis for recent clinical reports of increased mortality rates in patients taking digoxin in the setting of chronic heart diseases 4345 .…”
Section: Discussionsupporting
confidence: 57%
“…4,26 A recent metaanalysis described a risk of death associated with digoxin, especially in AF patients without HF. 27 In contrast, another one reported a neutral effect on mortality in AF patients with HF related to this drug. The latter study argued that excess in mortality related to digoxin could be due to a worse clinical profile such as more advanced stage of HF.…”
Section: Discussionmentioning
confidence: 98%
“…During recent years, systematic reviews of observational studies have compared digoxin versus no digoxin (the latter participants usually receiving some other treatment for heart rate control) in patients with atrial fibrillation or atrial flutter and showed that digoxin seemed to increase the risk of all-cause mortality regardless of concomitant heart failure [5356]. A systematic review of both observational studies and randomised clinical trials showed similar findings on all-cause mortality when assessing the observational studies.…”
Section: Why Is It Important To Do This Review?mentioning
confidence: 98%